High frequency impedance based fault location in distribution system with DGs - Jia, Ke; Ren, Zhefeng; Li, Lun; Xuan, Zhenwen; Thomas, David (Institution of Engineering and Technology, 2017)
Distributed generations (DGs) in the distribution systems are connected into the buses using power electronic converters. During fault, it is challenging to provide a constant impedance model for DGs in the system frequency due to the variable converter control strategies. System frequency impedance measurement based fault locations can be influenced by the converters’ fault behaviour. This study addresses this problem by proposing a wide-area high-frequency impedance comparison based fault location technique. The high-frequency impedance model of DG is provided. Based on the constant DG impedance model in high-frequency range, the faulted line sections can be distinguished by comparing the measured impedance differences without requiring the exact distribution system parameters. Simulation results show that the proposed wide-area transient measurements based fault location method can provide accurate faulted sections in the distribution systems with DGs regardless of the load and DG output variations, measurement noise, unbalanced loads and islanding operations.